1987
DOI: 10.1128/aem.53.3.615-617.1987
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of ajoene derived from garlic

Abstract: The antifungal activity of six fractions derived from garlic was investigated in an in vitro system. Ajoene had the strongest activity in these fractions. The growth of both Aspergillus niger and Candida albicans was inhibited by ajoene at <20 ,ug/ml.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(63 citation statements)
references
References 16 publications
5
58
0
Order By: Relevance
“…It follows that there may have been a direct antagonistic interaction between the EPF and the garlic extract in no-choice treatments. Extracts of Allium spp., like many other plant essentials, have been shown to contain antimicrobial and antifungal compounds (Yoshida et al, 1987;Pai & Platt, 1995;Bakkali et al, 2008). Spore germination experiments from substrate samples of no-choice terraria pointed in the same direction.…”
Section: Interactions Between Wireworms Epf and Garlic Extractmentioning
confidence: 66%
“…It follows that there may have been a direct antagonistic interaction between the EPF and the garlic extract in no-choice treatments. Extracts of Allium spp., like many other plant essentials, have been shown to contain antimicrobial and antifungal compounds (Yoshida et al, 1987;Pai & Platt, 1995;Bakkali et al, 2008). Spore germination experiments from substrate samples of no-choice terraria pointed in the same direction.…”
Section: Interactions Between Wireworms Epf and Garlic Extractmentioning
confidence: 66%
“…Extracts derived from true garlic have been shown to be antifungal to a variety of different fungi including Aspergillus (Pai and Platt 1995;Benkeblia 2004). In particular, allicin and ajoene (two major sulfur-containing organic compounds found in garlic bulbs; Ankri and Mirelman 1999) were found to be inhibitory towards species of Aspergillus (Yoshida et al 1987;Shadkchan et al 2004). Similarly, Lindsey and van Staden (2004) showed that extracts derived from T. violacea (wild garlic) also inhibited mycelial growth of several fungi.…”
Section: Discussionmentioning
confidence: 99%
“…At this stage, the active compounds that contribute to the antifungal nature of T. violacea are not known, and a mechanism therefore cannot be suggested. Several reports indicate that allicin and ajoene isolated from true garlic have antifungal (Yoshida et al 1987;Shadkchan et al 2004;Davis 2005) and antibacterial (Feldberg et al 1988;Naganawa et al 1996;Ankri and Mirelman 1999;Tsao and Yin 2001) activities, and it is possible that similar compounds may also be found in T. violacea.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments were found by a computer search (MEDLINE CD-ROM 1983-1989. Further experiments were found by checking references extensively and by personal communication with authors of experiments.…”
Section: Methodsmentioning
confidence: 99%
“…An increase of fibrinolytic activity was found in all three trials in which onions were used, while Table 1 Active principles of garlic and onions Anti-platelet: Garlic: alliin (Hanley & Fenwick, 1985) allicin (Block & Ahmad, 1984) allyl-1.5-hexadienyl-trisulphide (Block & Ahmad, 1984) allyl methyl trisulphide (Block & Ahmad, 1984) S-allyl 2-propene thiosulphinate (Block & Ahmad, 1984) ajoene (Apitz-Castro et al, 1984) diallyl disulphide (Ariga et al, 1981) diallyl trisulphide (Ariga et al, 1981) 1.5-hexadienyl-trisulphide (Apitz-Castro et al, 1983) methyl allyl trisulphide (Ariga et al, 1981) (Block, 1985) Onions adenoside (Kawakishi & Morimitsu, 1988) alliin (Liakopoulou-Kyriakides, 1985) 1-(methyl sulphinyl)-propyl methyl disulphide (Kawakishi & Morimitsu, 1988) 9,10,13-trihydroxy-11-octadecenoic acid (Ustunes et al, 1985) 9,12,13-trihydroxy-10-octadecenoic acid (Ustunes et al, 1985) trans-5-ethyl-4,6,7-trithia-2-decene-4-oxide (Bayer et al, 1988) trans,trans (and trans,cis) 5-ethyl-4,6,7-trithia-2,8-decadiene-4-oxide (Bayer et al, 1988) Antibiotic Garlic: allicin (Hanley & Fenwick, 1985) ajoene (Yoshida et al, 1987) diallyl disulphide (Amonkar & Reeves, 1971) diallyl trisulphide (Amonkar & Reeves, 1971) Fibrinolysis: Garlic: methane-thiol-3,4-dimethylthiophene (Augusti & Benaim, 1975) methyl cysteine sulphoxide (Augusti & Benaim, 1975) propyl allyl disulphide (Augusti & Benaim, 1975) propyl cysteine sulphoxide (Augusti & Benaim, 1975) Onions: cycloallUiin (August & Benaim, 1975) Blood sugar, insulin: Garlic: allicin (Hanley & Fenwick, 1985) diallyl disulphide (Hanley & Fenwick, 1985) Onions: allyl propyl disulphide (Augusti & Benaim, 1975) Blood lipids, cholesterol: Garlic: alliin (Kamanna & Chandrasekhara, 1984) allicin ...…”
Section: Fresh Onionsmentioning
confidence: 99%